Technologies of Using Communicative Exercises in the Development of Listening Skills - Shokirovna, Bazarbayeva Aziza (International Journal on Integrated Education, 2023)
This article under discussion depicts the importance of improving listening skills in preparing students to communication in English language. The author of the article analyses the ways of using listening exercises and presents technologies of organizing communicative activities for effective language acquisition.